2002
DOI: 10.2166/wst.2002.0060
|View full text |Cite
|
Sign up to set email alerts
|

From municipal sewage to drinking water: fate and removal of pharmaceutical residues in the aquatic environment in urban areas

Abstract: Recently, the occurrence and fate of pharmaceutically active compounds (PhACs) in the aquatic environment was recognized as one of the emerging issues in environmental chemistry and as a matter of public concern. Residues of PhACs have been found as contaminants in sewage, surface, and ground- and drinking water samples. Since June 2000, a new long-term monitoring program of sewage, surface, ground- and drinking water has been carried out in Berlin, Germany. Samples, collected periodically from selected sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
117
0
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(135 citation statements)
references
References 9 publications
6
117
0
4
Order By: Relevance
“…However, Schwarzenbach and colleagues also identified a group of organic chemicals (chloroform, 1,1,1-trichloroethane, trichloroethylene, and tetrachloroethylene) that were resistant to biological transformation and thus ineffectively removed by riverbank filtration. Indeed, some compounds are less affected by natural filtration, such as certain pesticides (24,29,31), pharmaceuticals (2,30,32), and halogenated organic compounds (23,28).…”
Section: Degrading Organic Contaminantsmentioning
confidence: 99%
“…However, Schwarzenbach and colleagues also identified a group of organic chemicals (chloroform, 1,1,1-trichloroethane, trichloroethylene, and tetrachloroethylene) that were resistant to biological transformation and thus ineffectively removed by riverbank filtration. Indeed, some compounds are less affected by natural filtration, such as certain pesticides (24,29,31), pharmaceuticals (2,30,32), and halogenated organic compounds (23,28).…”
Section: Degrading Organic Contaminantsmentioning
confidence: 99%
“…Pharmaceuticals are used throughout the world being not only applied in human medicine but also in livestock breeding and aquaculture (Heberer et al, 2002;Boxall et al, 2004). Many of the pharmaceutical drugs applied in human/animal medicine are not completely metabolized by the organism, being excreted as a mixture of the unchanged compound, metabolites (active or inactive) or conjugates (mostly glucuronides and sulfates) (Daughton and Ternes, 1999;Heberer et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the pharmaceutical drugs applied in human/animal medicine are not completely metabolized by the organism, being excreted as a mixture of the unchanged compound, metabolites (active or inactive) or conjugates (mostly glucuronides and sulfates) (Daughton and Ternes, 1999;Heberer et al, 2002). Once excreted, these drugs reach the environment directly or via Wastewater Treatment Plants (WWTPs), where the majority end up passing unaltered through the conventional removal treatments applied (Monteiro and Boxall, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The degree of removal of diclofenac in the treatment process varies considerably between individual wastewater treatment plants, depending on the used method and the treatment conditions such as season and temperature [4]. Major differences are present also in the results of research on methods of disposal, the degree of elimination of diclofenac ranging from 17 to 75% [5,6]. Ketoprofen is susceptible to photodegradation and other methods of treatment, nevertheless several studies indicate that the degree of ketoprofen removal is also highly volatile.…”
Section: Investigated Substancesmentioning
confidence: 99%
“…Widespread use of these drugs can lead to the penetration of their residues into wastewater as well as the natural environment [5]. Numerous studies have confirmed NSAIDs presence in effluents from sewage treatment plant [6].…”
Section: Introductionmentioning
confidence: 99%